Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the derivative of the function [tex]\( y = \frac{(1-x)^{20}}{(1+x)^{25}} \)[/tex] with respect to [tex]\( x \)[/tex], we need to apply the rules of differentiation. Let's break this down step by step.
### Step-by-Step Solution
1. Identify the Function to Differentiate:
We have [tex]\( y = \frac{(1-x)^{20}}{(1+x)^{25}} \)[/tex].
2. Apply the Quotient Rule:
The quotient rule states that if [tex]\( y = \frac{u(x)}{v(x)} \)[/tex], then:
[tex]\[ \frac{dy}{dx} = \frac{u'v - uv'}{v^2} \][/tex]
Here, [tex]\( u(x) = (1-x)^{20} \)[/tex] and [tex]\( v(x) = (1+x)^{25} \)[/tex].
3. Differentiate [tex]\( u(x) \)[/tex] and [tex]\( v(x) \)[/tex]:
- For [tex]\( u(x) = (1-x)^{20} \)[/tex]:
[tex]\[ u'(x) = \frac{d}{dx}[(1-x)^{20}] = 20(1-x)^{19} \cdot (-1) = -20(1-x)^{19} \][/tex]
- For [tex]\( v(x) = (1+x)^{25} \)[/tex]:
[tex]\[ v'(x) = \frac{d}{dx}[(1+x)^{25}] = 25(1+x)^{24} \][/tex]
4. Substitute [tex]\( u(x), u'(x), v(x), \)[/tex] and [tex]\( v'(x) \)[/tex] into the Quotient Rule:
[tex]\[ \frac{dy}{dx} = \frac{(-20(1-x)^{19})(1+x)^{25} - (1-x)^{20}(25(1+x)^{24})}{(1+x)^{50}} \][/tex]
5. Simplify the Expression:
Since the common denominator is [tex]\( (1+x)^{50} \)[/tex]:
[tex]\[ \frac{dy}{dx} = \frac{-20(1-x)^{19}(1+x)^{25} - 25(1-x)^{20}(1+x)^{24}}{(1+x)^{50}} \][/tex]
Factor out the common term in the numerator:
[tex]\[ \frac{dy}{dx} = \frac{(1-x)^{19}(1+x)^{24} \left[ -20(1+x) - 25(1-x) \right]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(1+x)^{24} \left[ -20 - 20x - 25 + 25x \right]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(1+x)^{24} \left[ -45 + 5x \right]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(-45 + 5x)}{(1+x)^{26}} \][/tex]
6. Further Simplify the Fraction:
Distribute the 5:
[tex]\[ = \frac{5(9 - x)(1-x)^{19}}{(1+x)^{26}} \][/tex]
This matches the simplified form [tex]\( 5 \cdot \frac{(9-x) (1-x)^{19}}{(1+x)^{26}} \)[/tex].
Thus, the derivative of [tex]\( y = \frac{(1-x)^{20}}{(1+x)^{25}} \)[/tex] is:
[tex]\[ \frac{dy}{dx} = \frac{-25 (1-x)^{20}}{(1+x)^{26}} - \frac{20 (1-x)^{19}}{(1+x)^{25}} \][/tex]
which simplifies to:
[tex]\[ \frac{dy}{dx} = 5 \cdot \frac{(9-x) (1-x)^{19}}{(1+x)^{26}} \][/tex]
Therefore, the correct answer matches:
[tex]\[ \boxed{-y\left(\frac{20}{1-x}+\frac{25}{1+x}\right)} \][/tex]
### Step-by-Step Solution
1. Identify the Function to Differentiate:
We have [tex]\( y = \frac{(1-x)^{20}}{(1+x)^{25}} \)[/tex].
2. Apply the Quotient Rule:
The quotient rule states that if [tex]\( y = \frac{u(x)}{v(x)} \)[/tex], then:
[tex]\[ \frac{dy}{dx} = \frac{u'v - uv'}{v^2} \][/tex]
Here, [tex]\( u(x) = (1-x)^{20} \)[/tex] and [tex]\( v(x) = (1+x)^{25} \)[/tex].
3. Differentiate [tex]\( u(x) \)[/tex] and [tex]\( v(x) \)[/tex]:
- For [tex]\( u(x) = (1-x)^{20} \)[/tex]:
[tex]\[ u'(x) = \frac{d}{dx}[(1-x)^{20}] = 20(1-x)^{19} \cdot (-1) = -20(1-x)^{19} \][/tex]
- For [tex]\( v(x) = (1+x)^{25} \)[/tex]:
[tex]\[ v'(x) = \frac{d}{dx}[(1+x)^{25}] = 25(1+x)^{24} \][/tex]
4. Substitute [tex]\( u(x), u'(x), v(x), \)[/tex] and [tex]\( v'(x) \)[/tex] into the Quotient Rule:
[tex]\[ \frac{dy}{dx} = \frac{(-20(1-x)^{19})(1+x)^{25} - (1-x)^{20}(25(1+x)^{24})}{(1+x)^{50}} \][/tex]
5. Simplify the Expression:
Since the common denominator is [tex]\( (1+x)^{50} \)[/tex]:
[tex]\[ \frac{dy}{dx} = \frac{-20(1-x)^{19}(1+x)^{25} - 25(1-x)^{20}(1+x)^{24}}{(1+x)^{50}} \][/tex]
Factor out the common term in the numerator:
[tex]\[ \frac{dy}{dx} = \frac{(1-x)^{19}(1+x)^{24} \left[ -20(1+x) - 25(1-x) \right]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(1+x)^{24} \left[ -20 - 20x - 25 + 25x \right]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(1+x)^{24} \left[ -45 + 5x \right]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(-45 + 5x)}{(1+x)^{26}} \][/tex]
6. Further Simplify the Fraction:
Distribute the 5:
[tex]\[ = \frac{5(9 - x)(1-x)^{19}}{(1+x)^{26}} \][/tex]
This matches the simplified form [tex]\( 5 \cdot \frac{(9-x) (1-x)^{19}}{(1+x)^{26}} \)[/tex].
Thus, the derivative of [tex]\( y = \frac{(1-x)^{20}}{(1+x)^{25}} \)[/tex] is:
[tex]\[ \frac{dy}{dx} = \frac{-25 (1-x)^{20}}{(1+x)^{26}} - \frac{20 (1-x)^{19}}{(1+x)^{25}} \][/tex]
which simplifies to:
[tex]\[ \frac{dy}{dx} = 5 \cdot \frac{(9-x) (1-x)^{19}}{(1+x)^{26}} \][/tex]
Therefore, the correct answer matches:
[tex]\[ \boxed{-y\left(\frac{20}{1-x}+\frac{25}{1+x}\right)} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.